Makna Pasal 18 Ayat (4) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (DiH: Jurnal Ilmu Hukum, 2023)
The purpose of this study is to find the meaning of Article 18 Paragraf 4 of the 1945 Constitution of the Republic of Indonesia. This research is legal research with a statutory, conceptual, and case approach. The results of this study found that Article 18 Paragraf 4 of the 1945 Constitution of the Republic of Indonesia was formulated flexibly with open texture and opened legal policy. Using the original intent of grammatical interpretation, it was found that 7 (seven) meanings of Article 18 Paragraf 4 of the 1945 Constitution of the Republic of Indonesia were 1) the regional head was the chief of local government, (2) Regional heads must exist and the number is 1 (one) person, (3) the deputy of regional head was not mandatory. If there can be 1 (one) or more people, (4) the regional head must be democratically elected, either directly by the people or by the local representative body, (5) the regional head candidate does not have to be submitted by a political party or a combination of political parties so that it can be an individual candidate, (6) the elected regional head is sufficient to obtain a simple majority of votes, and (7) the deputy of regional head is not obliged to be democratically elected, It is not mandatory to be selected in 1 (one) package of candidate pairs with the regional head, and can be appointed. Keywords: democratic; election; regional head Abstrak Tujuan penelitian ini adalah untuk menemukan makna Pasal 18 ayat (4) UUD NRI 1945. Penelitian ini adalah penelitian hukum dengan pendekatan perundang-undangan, konseptual, dan kasus. Hasil penelitian ini menemukan bahwa Pasal 18 ayat (4) UUD NRI 1945 dirumuskan secara fleksibel dengan sifat open texture dan opened legal policy. Dengan menggunakan penafsiran original intent gramtikal, ditemukan 7 (tujuh) makna Pasal 18 ayat (4) UUD NRI 1945 yakni 1) kepala daerah merupakan chief of local government, (2) kepala daerah wajib ada dan jumlahnya 1 (satu) orang, (3) wakil kepala daerah tidak wajib ada. Jika ada boleh 1 (satu) orang atau lebih, (4) kepala daerah wajib dipilih secara demokratis, baik secara langsung atau oleh DPRD, (5) calon kepala daerah tidak harus diajukan oleh partai politik atau gabungan partai politik sehingga boleh calon perseorangan, (6) kepala daerah terpilih cukup memperoleh simple majority suara, dan (7) wakil kepala daerah tidak wajib dipilih secara demokratis, tidak wajib dipilih dalam 1 (satu) paket pasangan calon dengan kepala daerah, dan dapat ditunjuk. Kata kunci: demokratis; kepala daerah; pemilihan